Bioassay-guided isolation of the antimicrobial compounds of Coleus amboinicus Loureiro (Lamiaceae) - Vasquez, E.A.; Kraus, W.; Conrad, J.; Volger, B.; Zebitz, C.; Rejesus, B.M. (Annals of Tropical Research, 2004)
The essential oil of the aerial part of Coleus amboinicus showed antibacterial activity against Bacillus subtilis (gram +) and Pseudomonas fluorescens (gram -) and antifungal activity against Cladosporium cucumerinum. Bioassay-guided fractionation revealed that carvacrol and ß-caryophyllene-4,5-oxide were the major contributors to the antimicrobial activity of the essential oil. The sesquiterpene α-humulene and monoterpenes α-pinene, α-terpmene and cymene present in significant amounts were inactive.